Meninjau Kembali Hak-hak Penyandang Disabilitas dalam Ranah Profesional - Mohammad Ulil Rosyad; Nur Rofiah; M. Darwis Hude; Dinan Kiasati (Lajnah Pentashihan Mushaf Al-Qur'an, 2026)
Persons with disabilities are often positioned within medical and charitable paradigms, which limit recognition of their capacities in public spaces, including the world of work. As a conceptual basis for fulfilling the professional rights of persons with disabilities, this article analyzes Surah ‘Abasa (80): 1–4. This study employs a qualitative approach through library research and applies the Socio-Religious Model of Disability (SRmD) by integrating the concepts of ahliyyah and maqasid asy-syari‘ah into the social model. The findings show that Surah ‘Abasa (80): 1–4 presents the neglect of Abdullah ibn Umm Maktum as related to a social perspective that evaluates a person based on bodily condition and social position. While the phrase “‘abasa wa tawalla” criticizes exclusion, “yazzakka” indicates that persons with disabilities possess the potential for self-development, knowledge acquisition, and social contribution. Therefore, the mention of “al-a‘ma” does not signify incapacity; rather, it affirms that physical limitation does not remove a person’s dignity, agency, ahliyyah, and professional capacity. The fact that Abdullah ibn Umm Maktum served as a muazzin, imam, and leader in Medina further strengthens the argument that persons with disabilities are entitled to employment access, reasonable accommodation, media adaptation, inclusive facilities, and legal protection.